Traders' Participation in Maintaining the Cleanliness of the Tondano Traditional Market Environment based on Presidential Decree number 112 of 2OO7 - Reynold Simandjuntak; Meiske Lasut; Novita Mongdong; Roof Pajow; Sariana Landaiyo; Romi Mesra (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This research aims to find out how traders participate in keeping the market environment clean, and what obstacles traders experience in keeping the market environment clean, as well as how traders overcome problems or obstacles in keeping the traditional market environment clean in Tondano City, North Sulawesi. The type of research used is qualitative. The collection techniques used in research are observation, interviews and documentation. As well as collecting data, researchers went directly into the field actively. Based on the results of research in the field and interviews, it is clear that some of the traders at the Tondano market have maintained the cleanliness of the environment in the market, and have prepared each trash bin in the place where they trade, and some traders have not participated in maintaining the cleanliness of the environment in the market, for example, they often throw away littering, and throwing away the remains of their trade everywhere.